The history of the University of Wisconsin-La Crosse Health Center, with special emphasis on 1975-85 - Berquam, L. M. (My University, 1986)
The purpose of this research was to provide a chronology of the university of Wisconsin-La Crosse Health bCenter, address the changes it has witnessed and suggest recommendations for the future of its status. the need for this research resulted from concerns pertaining to the increase in student enrollment and the budget cuts instituted for the Health Center operation. The research illustrated three era's of the Helath Center's progress, the three era's examined were 1918-1970 when the Health Center was first instituted, 1970-1978 when the Health Center was in the Grandview Building, and finally 1978-present when the Health Center was housed in the basement of Whitney Center.
Keywords: College students -- Health and hygiene -- Wisconsin -- La Crosse; University of Wisconsin Student Health Center -- La Crosse -- History